2014
DOI: 10.1111/bph.12721
|View full text |Cite
|
Sign up to set email alerts
|

TRP channels and STIM/ORAI proteins: sensors and effectors of cancer and stroma cell migration

Abstract: Cancer cells are strongly influenced by host cells within the tumour stroma and vice versa. This leads to the development of a tumour microenvironment with distinct physical and chemical properties that are permissive for tumour progression. The ability to migrate plays a central role in this mutual interaction. Migration of cancer cells is considered as a prerequisite for tumour metastasis and the migration of host stromal cells is required for reaching the tumour site. Increasing evidence suggests that trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 222 publications
0
45
0
Order By: Relevance
“…In contrast, it is conceivable that sublethal and localized ROS production, might initiate pro-tumorigenic Ca 2+ signaling via activation of cell surface Ca 2+ channels, such as proliferation [119], and wound healing [86]. In both oxidative stress and redox signaling, the location of cell surface Ca 2+ channels clearly makes these an excellent target for sensing redox changes in the intra and extracellular environment [120]. …”
Section: Redox Regulation Of Cellular Ca2+ Homeostasis At the Plasmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, it is conceivable that sublethal and localized ROS production, might initiate pro-tumorigenic Ca 2+ signaling via activation of cell surface Ca 2+ channels, such as proliferation [119], and wound healing [86]. In both oxidative stress and redox signaling, the location of cell surface Ca 2+ channels clearly makes these an excellent target for sensing redox changes in the intra and extracellular environment [120]. …”
Section: Redox Regulation Of Cellular Ca2+ Homeostasis At the Plasmentioning
confidence: 99%
“…Many of the stimulatory cues that activate plasma membrane channels are often altered in the tumor microenvironment and it is therefore conceivable that altered activity of plasma membrane associated Ca 2+ channels and pumps is a common phenotype of cancer cells[120]. Moreover, remodeling of ion channel expression and alterations in Ca 2+ signaling by plasma membrane cation channels, including TRPC1, TRPC3, TRPC6, TRPM2, TRPM7, TRPV6, ORAI1 and ORAI3 have been implicated in enhanced proliferation of tumor cells[16, 121].…”
Section: Redox Regulation Of Cellular Ca2+ Homeostasis At the Plasmentioning
confidence: 99%
“…[10]). Mammalian TRP proteins assemble as homo-or hetero tetramers and build non-selective Ca 2+ -permeable cation channels (refs.…”
Section: Plasma Membrane Calcium Channels and Transportersmentioning
confidence: 99%
“…TRP channels influence cancer and stroma cell migration via affecting growth factor and cytokine signaling, cytoskeletal remodeling, and adaptation to tumor microenvironment where oxidative stress and hypoxia occur [18].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies revealed that different TRP channels exhibit their effect on stromal cell migration via PI3K activation which is linked to reorganization of cytoskeleton and ERK signaling which regulates the actomyosin network [18]. Examples include TRPV2-dependent migration of macrophages [24], chemotaxis of monocytes relying on TRPC3 channels [25], TRPM7-dependent polarization and fibroblast migration [26], and TRPC6-dependent chemotaxis of neutrophils [27,28].…”
Section: Introductionmentioning
confidence: 99%